Some reflections on the markers of negation in Italian and Polish from a contrastive perspective - Kozakiewicz-Kłosowska, Dorota; Lewandowska, Małgorzata (Kwartalnik Neofilologiczny, 2026)
This paper examines negation in Italian and Polish from a contrastive-pragmatic perspective, focusing on its relevance for language teaching. Building on speech act theory (Austin 1962; Searle 1971, 1987) and classical studies of negation (Horn 1989), it argues that negation extends beyond logical opposition, functioning as a culturally shaped communicative strategy. The analysis highlights analogies and divergences between the two systems: Italian negation is pragmatically structured and mostly conventionalized to express irony, politeness, or emphasis; Polish relies on lexical and prosodic means and contextual interpretation. From a didactic viewpoint, the paper stresses the need to integrate grammatical and pragmatic dimensions through contrastive examples of negation.